Research on The Factors Influencing the Strike Price of Equity Option of Listed Companies in China. - Gong, Yixin (2021)
As an effective long-term incentive for listed companies, equity options have been proven in some developed countries. Therefore, under the unique national conditions of China and the existing state of the stock market, we cannot blindly introduce the stock option system of developed countries but should strengthen the research on the strike price of equity options of Chinese listed corporations, find the basis of the strike price pricing, and analyze the influencing factors of the strike price pricing. Establishing an exercise price pricing scheme that suits Chinese characteristics and establishing a more scientific option incentive mechanism is a concern for listed corporations in China. The research object is the equity option exercise spread of listed companies, and sample data are collected from 2011 to 2021. This research would break through the previous multiple regression and factor analysis methods, use the econometric software EViews10.0 as a tool and select several representative factors such as the listed companies' characteristics, the financial indicators, the governance structure, and the risk level to analyze the determinants of equity options’ strike price. The data of 123 listed firms with equity option plans in Shanghai and Shenzhen A-shares are tested for correlation and analyzed in a panel data model to study how the various influencing factors affect the strike price. The study also analyses the significance and importance of each element. It concludes to determine the factors listed companies should consider when pricing equity options to propose corresponding policy recommendations for relevant listed companies and government departments.